Circularly polarized light triggered enantioselective thiol–ene polymerization reaction. Issue 10 (20th January 2017) - Yang, Guang; Xu, Yang Y.; Zhang, Zi D.; Wang, Long H.; He, Xue H.; Zhang, Qi J.; Hong, Chun Y.; Zou, Gang
Abstract : Herein, circularly polarized light is utilized to trigger an enantioselective polymerization reaction, resulting in the synthesis of an optically active polymer from racemic monomers in the absence of any chiral dopant or catalyst. Abstract : Herein, circularly polarized light is utilized to trigger an enantioselective polymerization reaction, resulting in the synthesis of an optically active polymer from racemic monomers in the absence of any chiral dopant or catalyst.